2019
DOI: 10.1002/cam4.1971
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PTGS2/NF‐κB signaling pathway enhances radiation resistance of glioma

Abstract: Objective We focused on the effects of PTGS2/NF‐κB signaling pathway on the radiation resistance of glioma in the study. Methods We downloaded the microarray data from the Gene Expression Omnibus (GEO) database. We verified transfection successfully through QRT‐PCR analysis. Immunofluorescence was used to detect γH2AX content under 2 Gy radiation. The survival rates of cells under 2 Gy irradiation were tested by clonogenic survival assay. Flow cytometry was used to detect cell cycle. Western blot was applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Increasing evidence has suggested that rapid acquired therapeutic resistance is the major cause of the failure of standard comprehensive treatments, leading to the recurrence and high mortality of glioma . Various molecular pathways have been shown to be responsible for the acquisition of therapeutic resistance in glioma . Therefore, it is essential to identify the mechanisms, especially prognostic biomarkers, underlying therapeutic resistance in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has suggested that rapid acquired therapeutic resistance is the major cause of the failure of standard comprehensive treatments, leading to the recurrence and high mortality of glioma . Various molecular pathways have been shown to be responsible for the acquisition of therapeutic resistance in glioma . Therefore, it is essential to identify the mechanisms, especially prognostic biomarkers, underlying therapeutic resistance in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the problem with this therapeutic modality is that radiation effects vary dramatically among patients. Moreover, the effects of radiation therapy on radiation resistance are rarely studied [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…PTGS2 is one of the rate-limiting enzymes of synthesis of prostaglandins from arachidonic acid. In radiation-resistant glioma cells, PTGS2 expression is up-regulated and increased radio-tolerance by activating downstream signaling effectors NF-κB signaling [ 38 ]. NF-κB signaling is known to maintain the characteristics of CSCs associated with cancer progression.…”
Section: Discussionmentioning
confidence: 99%